Self and Family Management in Type 2 Diabetes: Influencing Factors and Outcomes. (July 2019) - Emery, Karin A.; Robins, Jo; Salyer, Jeanne; Thurby-Hay, Linda
Type 2 diabetes impacts over 30 million Americans and that number is increasing. Fundamental to optimal Type 2 diabetes control and improved health outcomes consists is effective self-management. There are several factors that promote and inhibit sustained and effective self-management. The established and evidence-based self and family management framework is proposed here as a solution for guiding research and practice to improve self-management and outcomes in patients with Type 2 diabetes.